PENGEMBANGAN PERANGKAT PERKULIAHAN ASPEK HUKUM DALAM INDUSTRI KONSTRUKSI MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD BERBANTUAN MIND MAP - Nanich Framulya (Indonesian Journal of Basic Education, 2020)
The purpose of this research is to produce a product in the form of lecture model of STAD type cooperative learning assisted by Mind Map in the Legal Aspect course, this type of research is development research. The development model used is the 4D model which consists of 4 stages, namely: defining, designing, developing and disseminating. This research was conducted with 30 students. This development process in the Construction Industry is valid, practical, and effective, using the STAD type cooperative learning model aided by Mind Map. The results showed that the lecture tools produced were valid, practical, and effective. This is seen based on the value of the validity, practicality and effectiveness of lecturing devices. The value of the validity of the set of lectures by experts is 0.89 valid categories and by practitioners is 0.91 valid categories. Practicality value is obtained from the Lecturer response questionnaire and Student response questionnaire. The practicality value by lecturers is 87.2% categorized as very practical. The practicality value by students is 89.2% categorized as very practical. The effectiveness value of the lecture set is obtained from the assessment of student activity and learning outcomes. The value of student attitudes is 75.82% categorized as very good, the average value of student knowledge is 80.00% categorized as good, and the average value of student skills is 76.73% categorized as good. Thus, this research has produced a lecture tool on Legal Aspects in the Construction Industry Using the STAD cooperative learning model assisted with Mind Map in the Legal, Legal Aspect in Construction Industry courses that are valid, practical, and effective.